Ancestors of two-spirits: Historical depictions of Native North American gender-crossing women through critical discourse analysis. Issue 3 (1st October 2016) - Hemmilä, Anita
ABSTRACT: Letters written by Christian men of European origin during the sixteenth–nineteenth centuries contain brief descriptions of gender-crossing individuals among indigenous Americans. Although now considered ethnocentrically biased because of the etic positioning of their authors, these historical sources are invaluable because they offer a glimpse of the ancestors of modern-day two-spirits. An application of critical discourse analysis to three depictions of gender-crossing females from the eighteenth and nineteenth centuries demonstrates that such women were favorably portrayed. These results differ dramatically from those obtained from my similar analysis of depictions of gender-crossing males. It also became evident that the three descriptions of gender-crossing women were not based on actual observations, but only on hearsay, which makes their use as primary sources questionable.